Genome-Wide Association Study and Identification of a Protective Missense Variant on Lipoprotein(a) Concentration: Protective Missense Variant on Lipoprotein(a) Concentration—Brief Report. Issue 5 (18th March 2021) - Said, M. Abdullah; Yeung, Ming Wai; van de Vegte, Yordi J.; Benjamins, Jan Walter; Dullaart, Robin P.F.; Ruotsalainen, Sanni; Ripatti, Samuli; Natarajan, Pradeep; Juarez-Orozco, Luis Eduardo; Verweij, Niek; van der Harst, P.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Lipoprotein(a) (Lp[a]) is associated with coronary artery disease (CAD) but also to LDL (low-density lipoprotein) cholesterol. The genetic architecture of Lp(a) remains incompletely understood, as well as its independence of LDL cholesterol in its association to CAD. We investigated the genetic determinants of Lp(a) concentrations in a large prospective multiethnic cohort. We tested the association for potential causality between genetically determined higher Lp(a) concentrations and CAD using a multivariable Mendelian randomization strategy. Approach and Results: We studied 371 212 participants of the UK Biobank with available Lp(a) and genome-wide genetic data. Genome-wide association analyses confirmed 2 known and identified 37 novel loci ( P <5×10 −8 ) associated with Lp(a). Testing these loci as instrumental variables in an independent cohort with 60 801 cases and 123 504 controls, each SD genetically elevated Lp(a) conferred a 1.30 ([95% CI, 1.20–1.41] P =5.53×10 − 11 ) higher odds of CAD. Importantly, this association was independent of LDL cholesterol. Genetic fine-mapping in the LPA gene region identified 15 potential causal variants. This included a rare missense variant (rs41267813[A]) associated with lower Lp(a) concentration. We observed a strong interaction between rs41267813 and rs10455872 on Lp(a) concentrations, indicating a protective effect of rs41267813(A). Conclusions: This study supports an LDL cholesterol–independent causal link between Lp(a) and CAD. A rare missense variant in the LPA gene locus appears to be protective in people with the Lp(a) increasing variant of rs10455872. In the search for therapeutic targets of Lp(a), future work should focus on understanding the functional consequences of this missense variant.